Tick-Borne Encephalitis Virus: A Comprehensive Review of Transmission, Pathogenesis, Epidemiology, Clinical Manifestations, Diagnosis, and Prevention - Emina Pustijanac; Moira Buršić; Jasminka Talapko; Ivana Škrlec; Tomislav Meštrović; Dubravka Lišnjić (Microorganisms, 2023)
Tick-borne encephalitis virus (TBEV), a member of the Flaviviridae family, can cause serious infection of the central nervous system in humans, resulting in potential neurological complications and fatal outcomes. TBEV is primarily transmitted to humans through infected tick bites, and the viral agent circulates between ticks and animals, such as deer and small mammals. The occurrence of the infection aligns with the seasonal activity of ticks. As no specific antiviral therapy exists for TBEV infection, treatment approaches primarily focus on symptomatic relief and support. Active immunization is highly effective, especially for individuals in endemic areas. The burden of TBEV infections is increasing, posing a growing health concern. Reported incidence rates rose from 0.4 to 0.9 cases per 100,000 people between 2015 and 2020. The Baltic and Central European countries have the highest incidence, but TBE is endemic across a wide geographic area. Various factors, including social and environmental aspects, improved medical awareness, and advanced diagnostics, have contributed to the observed increase. Diagnosing TBEV infection can be challenging due to the non-specific nature of the initial symptoms and potential co-infections. Accurate diagnosis is crucial for appropriate management, prevention of complications, and effective control measures. In this comprehensive review, we summarize the molecular structure of TBEV, its transmission and circulation in natural environments, the pathogenesis of TBEV infection, the epidemiology and global distribution of the virus, associated risk factors, clinical manifestations, and diagnostic approaches. By improving understanding of these aspects, we aim to enhance knowledge and promote strategies for timely and accurate diagnosis, appropriate management, and the implementation of effective control measures against TBEV infections.